1979
DOI: 10.1161/01.str.10.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Failure of thiopental to modify global anoxic injury.

Abstract: SUMMARY To corroborate thiopental protection from cerebral anoxia after cardiopulmonary arrest, 23 sedated, curarized, adult dogs were asphyxiated by plugging the endotracheal tube. Cardiopulmonary resuscitation (CPR) was started 7 minutes after electrocortical silence. Twelve animals received no other treatment (controls), 10 regained consciousness and spontaneous respirations, but remained decerebrate, blind, unable to drink or feed. Two dogs returned to a normal neurologic state. Ten dogs were treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1981
1981
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The degree of neurologic damage observed by Steen and Michenfelder was less than observed by Goldstein et al resulting in a reduction in the severity of neurologic damage between control and pentobarbital dogs. Snyder et al 20 reported that postinsult thiopental administration after asphyxial arrest in dogs failed to improve neurologic recovery. However, thiopental treated dogs suffered episodes of severe arterial hypotension with MAPs as slow as 20 torr during thiopental infusion.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of neurologic damage observed by Steen and Michenfelder was less than observed by Goldstein et al resulting in a reduction in the severity of neurologic damage between control and pentobarbital dogs. Snyder et al 20 reported that postinsult thiopental administration after asphyxial arrest in dogs failed to improve neurologic recovery. However, thiopental treated dogs suffered episodes of severe arterial hypotension with MAPs as slow as 20 torr during thiopental infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have documented a protective effect of various barbiturates in regional cerebral ischemia when they are administered before or shortly after the onset of ischemia or even after the end of ischemic insult (Smith et al, 1974; Hoff et al, 1975; Levy and Brierley, 1979). The effectiveness of barbiturates in ameliorating diffuse cerebral ischemia, however, is controversial, particularly when the ischemia is complete (Snyder et al, 1979; Steen et al, 1979). Complete cessation of cerebral blood flow (CBF) results in flattening of the EEG 15–20 s after the onset, in depletion of brain energy reserves, and in the attainment of plateau levels of lactate within 5–10 min (Lowry et al, 1964; Ljunggren et al, 1974), indicating that both energy‐producing and ‐utilizing reactions are arrested.…”
mentioning
confidence: 99%
“…In contrast, the protective efficacy of barbiturates following global cerebral ischemia is still somewhat controversial (Goldstein et al, 1966;Yatsu et al, 1972;Bleyaert et al, 1978;Steen et al, 1979;Snyder et al, 1979;Todd et al, 1982;Gisvold et al, 1984). In the initial studies of global ischemia, barbiturates administered prior to, during and post-cardiac arrest improved neurological outcome; however, later studies failed to show this same neuroprotective efficacy of barbiturates following global cerebral ischemia.…”
Section: The Rationale For Use Of Barbiturate Coma In Stroke?mentioning
confidence: 99%